Evaluation of small-capacity force transducers using a developed 2 N dead-weight type force standard machine - Junfang Zhu; Toshiyuki Hayashi; Koji Ogushi (SICE Journal of Control, Measurement, and System Integration, 2021)
A 2 N dead-weight type force standard machine (DWM) had been developed at the National Metrology Institute of Japan (NMIJ). Modifications of the force transducers and weight receivers of the DWM improved measurement reproducibility with rotational position change. Two modified small-capacity force transducers with rated capacities of 1 and 2 N could be precisely calibrated according to International Organization for Standardization (ISO) 376. The results showed quite smaller uncertainties in the calibration ranges of 100 mN to 1 N and 200 mN to 2 N than the catalogue accuracies of commercial transducers. The validity of the calibration capability of the 2 N DWM was confirmed by comparing it with a 50 N DWM. The results obtained by two DWMs coincided within the uncertainties of calibration.